Effectiveness of Chinese Herbal Medicine Combined with Antibiotics for Extensively Drug-Resistant Enterobacteria and Nonfermentative Bacteria Infection: Real-Life Experience in a Retrospective Cohort. (11th October 2017) - Cai, Yangping; Zhang, Qing; Fu, Yuefeng; Li, Li; Zhao, Ning; Lu, Aiping; Liu, Qingquan; Jiang, Miao
Abstract : Chinese herbal medicines (CHMs) have been successfully used in the treatment of infectious diseases, yet the effectiveness of CHMs for extensively drug-resistant enterobacteria (XDRE) infection remains unclear. Herein we developed a retrospective multicenter study including 766 patients with XDRE and nonfermentative bacteria (NFB) infection to investigate the effectiveness of CHMs combined with antibiotics in the treatment of XDRE infections in clinical daily practice in a cohort of patients and compared the regular antibiotics monotherapy. After 14-day treatment, the 547 patients accepted CHMs combined with antibiotics therapy indicating a more desirable effectiveness compared to the 219 patients treated with antibiotics monotherapy. The primary evaluation indexes included white blood cell count (WBC) and percentage of neutrophil (N%) in blood test. Secondary evaluation indexes consisted of body temperature, breath, heart rate, platelets, hemoglobin, red blood cell, albumin, creatinine, glucose, and 28-day survival rates. Briefly speaking, in our experience, CHMs combined with antibiotics therapy achieved more desirable effectiveness in treating XDRE infections compared with antibiotics monotherapy, and CHMs might be a potential huge resource in the field of XDRE infection management and enlighten the new antibiotics research and development. This trial is registered with ChiCTR-ORC-17011760 .